PENINGKATAN IMUNITAS BENIH IKAN KERAPU LUMPUR, Epinephelus coioides TERHADAP INFEKSI VIRUS IRIDO DENGAN APLIKASI VITAMIN C DAN BAKTERIN - Fris Johnny; Des Roza; Agus Priyono (Jurnal Perikanan Universitas Gadjah Mada, 2008)
An  experiment  to  increase  of  immune  system  of  mangrove  grouper,  Epinephelus coioides seed with application of vitamin C and immunostimulant have been done. The experiment was carried out in completely randomized design with three treatments in twoplicates. The mangrove grouper seed (5 cm total length) were treated with 1000 mg vitamin C/kg diet (A), 1000 mg vitamin C + 1 ml bacterin/kg diet (B), and control (C). Vitamin C and bacterin were given every 10 day during 60 days rearing. After 30 and 60 days fishes were challenged with irridovirus. At the end of experiment, the non-specific immune responses were examined. The result showed that at challange test I, the highest survival rate was at treatment B (56.6%), followed by A (55.0%) and control (41.7%). On challenge test II, the higest survival rate was at treatment B (76.7%) followed by treatment A (68.4%) and control (48.3%).  The highest phagocytic activity (PA) was obtained at treatment B (21.0%), followed by treatment A (18.5%) and control (9.5%). The highest of lysozyme activity (LA) value was obtained on treatment B (2.0 cm), followed by treatment A (1.9 cm) and control (1.3 cm).  Combination of addition of ascorbic acid and immunostimulant gave higher survival rate compared to addition of immunostimulant only and control. Non-spesific immune response of mangrove grouper fry was significant different among treatment (P<0,05).